1st Symposium on Advances in Educational Technology: Outlook - Serhiy Semerikov; Viacheslav Osadchyi; Olena Kuzminska (Academy of Cognitive and Natural Sciences, 2021)
This is an overview of the Proceedings of the 1st Symposium on Advances in Educational Technology (AET 2020), which was held in Kyiv, Ukraine, on November 12-13, 2020. It includes an introduction, a summary of the papers, and some reflections on the event and its future.